Gesture As Sign: A Semiotic Analysis of Bengali Everyday Emblematic Hand Gesture - Jahan, Tawhida (Social Science Review, 2025)
Emblematic hand gestures or emblems always possess human beings’ communicative intentions. As signs, people worldwide use this gesture category in their everyday communicative contexts instead of words or phrases. Bengali Everyday Emblematic BEE hand gestures, a regional form of emblem, are also potentially enough for this purpose. This article examines the nature of BEE hand gestures as tools of communication in the context of Bengali-speaking areas. Seventeen (17) university students participated in this study to decode images of selected BEE hand gestures. The result of this study states that though all BEE hand gestures are used as dedicated communicative tools, some of these are identified as ‘absolute emblems’, and a few of these as ‘deviated emblems’. Additionally, individuals from the Bengali gesture community feel comfortable using these BEE hand gestures in their everyday communication. Social Science Review, Vol. 42(1), June 2025, pp. 101-112